Fire and ice: a gold(III) monohydride - Hashmi, A. Stephen K. (Angewandte Chemie. International edition, 2012)
Good as gold: Gold hydrides were long considered unstable. In the past few years reports have appeared on not only the stable NHC gold(I) monohydride complex 1 (see structure; NHC=N-heterocyclic carbene) but also a dinuclear gold(I) hydride and most recently the gold(III) monohydride complex 2 with a C-N-C pincer ligand. One can expect new and important impulses for inorganic and organometallic chemistry and homogeneous gold catalysis.